Ironless Loudspeakers with Ferrofluid Seals - RAVAUD, Romain; LEMARQUAND, Guy; LEMARQUAND, Valérie; DEPOLLIER, Claude (Archives of Acoustics, 2008)
This paper describes the drawbacks related to the iron in the classical electrodynamic loudspeaker structure. Then it describes loudspeaker motors without any iron, which are only made of permanent magnets. They are associated to a piston like moving part which glides on ferrofluid seals. Furthermore, the coil is short and the suspension is wholly pneumatic. Several types of magnet assemblies are described and discussed. Indeed, their properties regarding the force factor and the ferrofluid seal shape depend on their structure. Eventually, the capacity of the seals is evaluated.